2000
DOI: 10.3758/bf03205558
|View full text |Cite
|
Sign up to set email alerts
|

Categorical perception occurs in newly learned faces, other-race faces, and inverted faces

Abstract: On the basis of findings that categorical perception (CP) is possible in complex visual stimuli such as faces, the present study tested for CP on continua between unfamiliar face pairs. Results indicate that CP can be observed for unfamiliar faces, in both familiar (same-race) and unfamiliar (other-race) groups. In addition, significant CP effects were observed in inverted faces. Finally, half-continua were tested where midpoint stimuli became endpoints. This was done to ensure that stimulus artifacts did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
129
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 40 publications
11
129
3
Order By: Relevance
“…Four experiments with faces support the original interpretation of categorical perception (CP) as only present for familiar categories. Unlike in the results of Levin and Beale (2000), no evidence is found for face identity CP with unfamiliar faces. Novel face identities were shown to be capable of encoding for immediate sorting purposes but the representations utilized do not have the format of perceptual categories.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…Four experiments with faces support the original interpretation of categorical perception (CP) as only present for familiar categories. Unlike in the results of Levin and Beale (2000), no evidence is found for face identity CP with unfamiliar faces. Novel face identities were shown to be capable of encoding for immediate sorting purposes but the representations utilized do not have the format of perceptual categories.…”
contrasting
confidence: 54%
“…CP has been demonstrated for initially unfamiliar faces (Goldstone, Lippa, & Shiffrin, 2001;McKone, Martini, & Nakayama, 2001;Viviani, Binda, & Borsato, 2007) but training in McKone et al (2001) was extensive (between 1,000 -10,000 trials; 2 -14 hr /participant/face pair) and considerable (15 min of similarity ratings plus 54 trials for each of four faces in a category learning task in Goldstone et al, 2001; thousands of preliminary identification trials on the morphed continua in Viviani et al, 2007). However, there are reports that brief exposure to unfamiliar faces can result in CP (Campanella, Hanoteau, Seron, Joassin, & Bruyer, 2003;Levin & Beale, 2000).…”
mentioning
confidence: 99%
“…Keil (1995, 1996) found that participants show categorical perception for continua between familiar faces. Levin and Beale (2000) found heightened discriminability at category boundaries even for unfamiliar and inverted faces, and conclude that such effects are based on the rapid learning of perceptual categories. Particularly strong categorical perception effects have been found when researchers have used similarity ratings rather than psychophysical measures of discriminability.…”
Section: Introductionmentioning
confidence: 69%
“…Whereas some researchers have found the primary impact of category learning to be decreasing people's confusions when making discriminations involving perceptual dimensions relevant to the categorization (Goldstone, 1994a;Levin & Beale, 2000), other researchers have found category learning to primarily increase similarity ratings between objects belonging to the same category (Kurtz, 1996;Livingston et al, 1998). One possible reason for this may be that psychophysical measures of discriminability seem to promote expansion whereas similarity ratings promote compression (Levin & Beale, 2000). Another proposed resolution is that if the categorized objects are extremely similar, then expansion is found; otherwise, compression is found (Livingston et al, 1998).…”
Section: How Does Categorization In¯uence Judgments?mentioning
confidence: 99%
“…Other research has shown that prolonged experience with a domain such as dogs (Tanaka & Taylor, 1991) or faces (Levin & Beale, 2000;O'Toole, Peterson, & Deffenbacher, 1995) leads to development of a perceptual system that is tuned to these domains. Goldstone et al (2000) review other evidence for conceptual influences on visual perception.…”
Section: Connecting Concepts To Perceptionmentioning
confidence: 99%